Children's Mentality in the Stories of Shukur Kholmirzayev - Khamidova Sabrina Zarifovna (Open Academia, 2023)
In this article, Shukur Kholmirzayev tried to reveal the subtle aspects of the psyche of children, especially teenagers
Keywords: Shukur Kholmirzayev; human psyche; artistic work